Post TAVR coronary revascularization guided by stress cardiac imaging and impact on cardiovascular events. (25th November 2020) - Lattuca, B; Prunet, E; Huet, F; Akodad, M; Manna, F; Macia, J.C; Schmutz, L; Gandet, T; Cayla, G; Leclercq, F
Abstract: Background: The prognostic impact of systematic revascularization of asymptomatic coronary artery stenosis before transcatheter aortic valve replacement (TAVR) is still debated Purpose: The main objectives of this study were to evaluate the feasibility and the safety of a functional evaluation of coronary artery disease (CAD) followed by a selective ischemia-guided percutaneous coronary intervention (PCI) after TAVR. Methods: This prospective, bi-centric, one-arm, open-label trial included patients with severe aortic stenosis (AS) eligible for TAVR and with significant CAD defined as one or more coronary stenosis ≥70%. Patients with left main stenosis ≥50%, proximal left anterior descending artery (LAD) stenosis ≥90% or > class 2 Canadian cardiovascular society angina pectoris were excluded. Coronary revascularization was not performed before TAVR and myocardial ischemia was evaluated by stress cardiac imaging one month after the procedure using Single-Photon Emission Computed Tomography Myocardial Perfusion Imaging or Stress Echocardiography using dobutamine infusion. The primary endpoint was the composite of all cause of death, stroke, major bleeding (Bleeding Academic Research Consortium (BARC) ≥3), major vascular complication (Valve Academic Research Consortium 2 criteria), myocardial infarction (MI) and hospitalization for cardiac causes at 6 months following TAVR. Results: Between June 2016 and March 2019, 71 patients were included with a complete follow-up in 66 patients. The mean age was 84±5.2 years and the mean Euroscore was 13±8.6. Stress cardiac imaging could be achieved in 70% (n=46) of the patients and the main causes to not perform it were patient refusal or secondary impaired medical condition. Significant myocardial ischemia was observed in only 3 patients (4.5%), of whom 2 patients had successful PCI. The primary endpoint occurred at 6 months in 15 patients (23%) including death in 6 patients (9%), stroke in 3 patients (5%) and major bleedings in 3 patients (5%). Acute MI was observed in only 2 patients (3%) that had not-LAD proximal and severe coronary stenosis (≥90%). Hospital readmission (n=27, 41%) was mostly related to non-cardiac causes (n=18, 27%). Conclusions: In patients scheduled to TAVR and with significant coronary disease, a strategy of selective ischemia-guided coronary revascularization after TAVR appears safe with a low rate of myocardial infarction and myocardial ischemia requiring revascularization during follow-up. However, the poor adherence of elderly patients to stress test could suggest to perform PCI of proximal and severe coronary lesions. Large-scale and randomized trials are warranted to validate this strategy. Funding Acknowledgement: Type of funding source: None